2015
DOI: 10.1039/c5tb00705d
|View full text |Cite
|
Sign up to set email alerts
|

Differential sub-cellular processing of single-wall carbon nanotubes via interfacial modifications

Abstract: Strategies for cell-specific targeting and delivery of carbon nanotubes have made significant advancements over recent years. However, control of sub-cellular localization, an important criterion for many biomedical applications, remains largely unexplored. In this work, we experimentally demonstrate how different molecules that are used to non-covalently suspend hydrophobic SWCNTs in aqueous conditions also influence cellular processing and localization. We utilized complementary imaging modalities to show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Thus, the bright regions of fluorescence are most likely the peptide‐functionalized rCG materials. Overall, the imaging demonstrated that the peptide‐functionalized rCG materials were compatible at the sub‐cellular level, and this is important since other bionanoparticles have been shown to associate with and/or alter the structure of the nucleus, cytoskeleton and mitochondria . We contend that the reduced nature of GO along with the compatible peptides result in a material that is well tolerated by cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the bright regions of fluorescence are most likely the peptide‐functionalized rCG materials. Overall, the imaging demonstrated that the peptide‐functionalized rCG materials were compatible at the sub‐cellular level, and this is important since other bionanoparticles have been shown to associate with and/or alter the structure of the nucleus, cytoskeleton and mitochondria . We contend that the reduced nature of GO along with the compatible peptides result in a material that is well tolerated by cells.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report by Holt et al has shown that SWCNTs that were dispersed in bovine serum albumin (BSA) altered the ER distribution of the cells. 39 The colocalization of ER and mitochondria indicates apoptotic Ca 2+ release followed by cell death. During this process ceramide production and phosphatidylinositol production increases, both of which induce certain lipid kinases and several cell-death related pathways.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2024 It is now known that anionic nanotube dispersions ( e.g. , ssDNA-dispersed SWCNTs) enter cells by means of an energy-dependent endocytic mechanism 21,25,26 and exhibit low cytotoxicity.…”
mentioning
confidence: 99%